Familias Disfuncionales Y Autoestima en los Estudiantes de Educación General Básica de la Unidad Educativa“Juan de Velasco” Sede 2. Riobamba. Octubre 2017-Marzo-2018 - Flores Tapia, José Eduardo (2018)
Family dysfunctionality is relevant to self-esteem, which is why the present investigation aimed to analyze the relationship of dysfunctional families in the self-esteem of the Seventh year of Basic General Education of the Educational Unit Juan de Velasco SEDE 2, the methodology that was used was non-experimental design, with a type of research, cross-sectional, bibliographic and field, the level of research was descriptive, explanatory and correlational, with an Inductive-Deductive research method, the population were the students of the Unit Educative Juan de Velasco SEDE 2, the sample was not probabilistic and intentional since it was worked with 100 students, the techniques that were used were the survey and the psychometric test, the instruments were the Ah questionnaire. Doh and the questionnaire A-EP of self-esteem, the collection and obtaining of the data helped us to carry out the respective analysis of the results, in order to reach the conclusion that there is a relationship between dysfunctional families and the self-esteem of the students, since the students that belong to this type of families present a medium and low level, since the relationship between their parents is poor due to lack of communication and free time.